(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Background:Obstetric fistula (OF) is not very uncommon in our country. But recent issue of increase in iatrogenic fistula (IF) creates a field of interest. Objective:To find out the frequency and the cause of iatrogenic genitourinary fistula admitted in National Fistula Centre (NFC), Dhaka. Methods:This prospective study was conducted in NFC, Dhaka from January, 2010 to December, 2012. All cases admitted during the study period were included in this study. All patients were evaluated through detailed history, physical examination, relevant investigations and examination under anaesthesia (EUA). Repair was done through abdominal or vaginal route based on the findings. Results of repair were noted and analyzed. Results:On an average more than 20% cases of genitourinary fistula (GUF) were due to iatrogenic causes. Among them about 90% cases had history of hysterectomy as an offending procedure. A rising trend of iatrogenic fistula is observed with 19.04% in 2010, 15.68% in 2011 and 30% in 2012. Conclusion:This study shows that iatrogenic injuries in women under 40 years of age form major share in the aetiology of GUF. Iatrogenic fistula are increasing day by day. It is the time to check the experience of surgeons doing the gynecological and obstetrical surgeries in a developing country like ours. Bangladesh J Obstet Gynaecol, 2017; Vol. 32(1): 10-13